The efficiency of nitrogen retranslocation from leaf biomass in Quercus ilex ecosystems (Plant Ecology, 1992)
Nitrogen retranslocation from senescing leaves represents a crucial adaptation by tree species towards a more efficient use of this nutrient. As a result, this part of the nitrogen cycle has received increasing attention in recent years. However, there remain strong discrepancies with respect to the factors re- sponsible for interspecific differences in the efficiency of this process. In the present work the seasonal pattern of leaf growth and the movement of nitrogen in leaves have been studied in a series of Quercus ilex plots with different levels of rainfall and soil quality in central- western Spain, as well as in 20 other woody species typical of this area. The percentage of nitrogen retranslocated was estimated from the difference between the maximum mass of nitrogen stored in the leaf biomass and the amount of this nutrient returned annually to the soil through leaf fall. Q. ilex appears as one of the least efficient species in the Mediterranean region in the recovery of nitrogen from senescing leaves (29.7°0 of the maximum pool). Furthermore, the older leaves of Q. ilex do not s h o w the cycles of nitrogen withdrawal during new flushes of shoot growth, such as occurs in Pinus spp. This suggests that older leaves in Q. ilex do not play an important role as nitrogen storage organs.